P195 Diagnosing recent HIV infection in an urban sexual health centre: could more have be done to prevent acquisition?. (30th June 2016) - Walker, Eliza; Gilson, Rebecca; Fernando, Imali
Abstract : Background/introduction: There are a number of strategies that may be employed by sexual health services to prevent HIV transmission, including motivational interviewing and Pre-Exposure Prophylaxis (PrEP). In order to utilise resources effectively, prevention strategies need to target those at high risk of acquiring HIV such as those having unprotected anal sex or who had known rectal infections. Aim(s)/objectives: We aimed to identify individuals in our cohort diagnosed with recently acquired HIV infection, review whether they had previously been accurately identified as high risk and what strategies had been employed to attempt reduce their risk. Methods: Electronic records of patients diagnosed HIV positive at an urban sexual health centre over a two year period were reviewed for timing of acquiring infection and previous engagement with sexual health services. Recently acquired infections were determined by: positive avidity, a negative test or a history of seroconversion symptoms in the 6-months prior to positive result. Results: 68 patients were diagnosed with HIV; 30 (44.1%) were recently acquired infections. Of these, 13 (43.3%) had attended a sexual health service in the year prior, 12 (92%) of whom had been identified as at risk and had risks discussed by a healthcare professional. Discussion/conclusion: Almost half of our patients with recently acquired HIV had had contact with sexual health services in the year before their diagnosis, and the vast majority were identified at high risk. Being able to correctly identify patients at high risk of HIV has implications for using strategies such as PrEP in the future.